2021
DOI: 10.1177/13506501211010030
|View full text |Cite
|
Sign up to set email alerts
|

Churning power loss of the intermediate gearbox in a helicopter under splash lubrication

Abstract: Based on computational fluid dynamics, a two-phase flow model was established to calculate the churning power loss of the spiral bevel gears under splash lubrication. The error between the simulation results and experiment results is only 7.04%. Taking a certain helicopter as an example, the churning power loss of the intermediate gearbox is ∼2.6051 kW, accounting for ∼1.93% of the input power. Besides, the motion mechanisms of free flow, ejection flow and splashing flow of the spiral bevel gear were investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…They found that the structural aperture of the oil guide device and the radius of the oil duct have important influences on the oil supply of the bearing, but have minor effects on the churning loss and the lubrication of the gear meshing zone. Lu et al [32] established a CFD model of oil-air two-phase flow for the intermediate gearbox used in helicopters. According to the oil flow characteristics, the lubricating oil stirred by the gear is divided into free flow, jet flow and splash flow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the structural aperture of the oil guide device and the radius of the oil duct have important influences on the oil supply of the bearing, but have minor effects on the churning loss and the lubrication of the gear meshing zone. Lu et al [32] established a CFD model of oil-air two-phase flow for the intermediate gearbox used in helicopters. According to the oil flow characteristics, the lubricating oil stirred by the gear is divided into free flow, jet flow and splash flow.…”
Section: Introductionmentioning
confidence: 99%
“…Although the authors of the above literature have carried out relevant research on the lubrication characteristics of the splash-lubricated bevel gear transmission system, the numerical model used for research is quite different from the actual model. Compared with the gears in the engineering model, the gears in References [30][31][32][33][34][35][36][37] are all reduced, and therefore cannot reflect the real tooth surface shapes and meshing relationships. In addition, in order to reduce the pre-processing of the model and the number of grids used for numerical calculation, a box with a relatively simple shape is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…As for the complex spiral bevel gears, Hu et al [8,9] and Jiang et al [10] quantitatively analyzed the influence of rotating speed, oil guide device, and dynamic attitudes on the churning losses of spiral bevel gears in the intermediate or tail gearbox of a helicopter using the CFD method. Lu et al [11] also investigated the effects of the rotating speed and oil immersion depth of spiral bevel gears in the intermediate gearbox, and further recommended the speed and depth range on the basis of the balance between sufficient lubrication and low churning losses. Using the smoothed particle hydrodynamics method, a similar study was also conducted by Legrady et al [12].…”
Section: Introductionmentioning
confidence: 99%
“…Tetrahedral meshes are characterized by higher generation times with respect to prismatic or hexahedral elements. Single rotating helical gears [11] and spiral bevel gears [12] have been already simulated by the authors, while the virtual modelling of mating gears has been approached with mesh [13][14][15][16][17][18][19][20] and meshless methods [21][22][23][24][25][26] in commercial software. Works based on a general procedure in open-source software are still lacking in the literature.…”
Section: Introductionmentioning
confidence: 99%